Associations between language acculturation, age of immigration, and obesity in the Mexican American Mano A Mano cohort. Issue 5 (September 2017) - Chrisman, Matthew; Chow, Wong-Ho; Daniel, Carrie R.; Wu, Xifeng; Zhao, Hua
Highlights: Healthy behaviors and health outcomes such as BMI status become more unfavourable in Mexican–Americans as they become more acculturated. Little is known about the role of language acculturation in the development of obesity. Language acculturation may play a role in the development of unhealthy outcomes like obesity in this population, particularly for those born in the U.S. Sitting time mediates this association. Summary: Introduction: As Mexican immigrants to the U.S. become acculturated, they face worsening health outcomes such as obesity. The role of language acculturation in the development of obesity has not been thoroughly examined. Methods: To examine associations between language acculturation and obesity, data were drawn from the Mexican–American Mano A Mano cohort study. Participants aged 20 years and over (n = 18, 298) completed baseline questionnaires on socio-demographic and behavioural factors, including physical activity and sitting time. The Bi-dimensional Acculturation Scale for Hispanics assessed language acculturation. Multivariate-adjusted logistic regression was conducted to investigate associations between language acculturation, immigration age, and obesity, and whether sitting time and physical activity mediated these associations. Results: Individuals with obesity were more linguistically acculturated than individuals who were normal weight or overweight ( P < 0.001); however, this relationship differed by gender and nativity. Among Mexico-born women, language acculturation score was inversely related to BMI ( P < 0.001). Language acculturation was associated with higher risk of obesity (OR = 1.35, 95% CI: 1.12–1.62) in U.S.-born participants and lower risk in Mexico-born participants (OR = 0.90, 95%CI = 0.81–1.00). For Mexico-born participants, arrival in the U.S. as an adult (≥20 years old) was associated with a reduced obesity risk (OR = 0.74, 95% CI: 0.67–0.80). Sitting time mediated the association between language acculturation and obesity. Conclusions: Language acculturation may influence obesity development among the U.S.-born Mexican Americans in this cohort, but not their Mexico-born counterparts. Sitting time could be targeted in obesity prevention efforts in this population.